Recruitment and engagement of a cohort of women living with HIV in Nigeria: Baseline characteristics from the Nigeria Implementation Science Alliance. - Nwamaka Alexandra Ezeonu; John Olajide Olawepo; Uche Okezie; Emmanuel Egbo; Ijeoma Uchenna Itanyi; Ahmad Aliyu; Tonia C Onyeka; Babayemi Oluwaseun Olakunde; Collins Imarhiagbe; Stephen Tersoo Orafa; Samuel Cheure; Uduak Akpan; et al. (PLOS Global Public Health)
Nigeria has a high burden of mother to child transmission (MTCT) of HIV. There is paucity of large-scale prospective cohort studies to provide insight into the reasons for the abysmal MTCT indices. This paper describes the baseline characteristics of women living with HIV who signed consent to participate in future clinical or implementation trials. The Nigeria Implementation Science Alliance (NISA) developed an open multicentre prospective cohort of women of reproductive age living with HIV, drawn from 12 facilities across the six geo-political regions of Nigeria. Research Electronic Data Capture system was used for the informed consent process. Socio-demographic and clinical information of participants were accessed through the clinics' Electronic Medical Records. We calculated descriptive statistics, summarizing categorical variables using frequencies and percentages. Numerical variables were summarized using means and standard deviations for normally distributed, and median and interquartile ranges for skewed variables. We recruited 18,210 women living with HIV. Eighty-one percent (14,777/18,210) had their data extracted from the EMR. Data of 10,996 women were analysed. The mean age was 37.4 ± 7.2 years, with 85% in age groups ≥30-39 years. The median time since HIV diagnosis was 8 years (IQR 3-11 years) while the median length of time on ART was 6 years (IQR 3-10 years). For women who had a record of WHO clinical staging and most current viral load, majority (80%) were in WHO stage 1 while two thirds (68.0%) had viral load of <20 copies/mm3. Almost all women (94%) were on first-line antiretrovirals, with none on the third-line regimen. This unique cohort in Nigeria that will provide researchers with a platform to propose and answer several research questions about the health of women and infants providing policymakers with information on maternal and child health in Nigeria.